Pelatihan Kerja Berbasis Syariah untuk Atasi Pengangguran di Kebon Kopi Desa Puspanegara, Citeureup, Kabupaten Bogor - Parida, Ida; Prasetyo, Agung; Damayanthi, Dessy (Al-Wasathiyah: Journal of Islamic Studies, 2023)
The background of this research is the impact of termination of employment which resulted in a large number of unemployment rates, especially in the kp kebon kopi area, is a difficult problem to solve. Therefore, preparing quality human resources is very important so that the only way to solve existing problems is by empowering people with improve the quality of human resources conducting job training in coffee plantations, namely humans are able to carry out all activities that have activities to provide services or work businesses that are effective and efficient etc. Limiting this problem is an effort to increase human resources to overcome unemployment through job training in an Islamic perspective. The formulation of this problem is how to increase human resources in order to overcome unemployment and how Islam views unemployment. The role of the environment in Kp Kebon Kopi and to find out how Islam views unemployment. Theoretically, this research can add knowledge and insight, especially regarding the Job Training program to increase human resources and reduce unemployment. In addition, this research can be used as reading material, references, and studies. Practically, it can provide quality input to the community and place of training in implementing job training. So that it can increase human resources and reduce unemployment in the Kp Kebon Kopi environment. This study uses a qualitative method. Data collection is done by the method of observation, interviews and documentation. Analysis of data by collecting data and presenting data. The results of the research at the job training site in Kebon Kopi are that in increasing human resources in order to overcome unemployment, there must be quality human resources provided for example by someone providing services or businesses that are effective and efficient, etc. The number of unemployment rates in Kp Kebon Kopi every year increases but with the job training program in the coffee plantation environment it shows a very petrified role with the achievement of an increase in the workforce but job training efforts in reducing the number of unemployment rates have not gone well, if the number of workers has increased every year, of course, the number of labor force should decrease and the unemployment rate will decrease every year. However, this is reversed, namely the number of labor and unemployment will both increase.